Exploration of Mathematical Concepts in Slobog Solo Batik Motifs - Novani, Jihan; Nurcahyo, Adi; Setyaningsih, Rini (Universitas Muhammadiyah Surakarta, 2026)
Previous ethnomathematics studies on Indonesian batik have largely concentrated on widely recognized motifs, resulting in limited scholarly attention to several classical motifs that possess distinctive visual and philosophical characteristics. Batik Slobog Solo is one such motif that remains underexplored from a mathematical perspective. This study aims to investigate and describe the mathematical concepts embedded within the Batik Slobog Solo motif as a foundation for developing culturally contextualized mathematics learning. The research adopts a qualitative design employing an ethnographic approach, with data collected through observation, semi-structured interviews, and documentation at the Danar Hadi Batik Museum in Surakarta. The exploration process follows four guiding questions: “Where do I start looking?”, “How do I find it?”, “How do I know that I have found something significant?”, and “How to understand it?”. The findings indicate that Batik Slobog Solo embodies various mathematical concepts, including plane geometry and transformational geometry, arithmetic patterns represented through square numbers and arithmetic sequences, as well as discrete mathematics concepts involving tiling and graph theory. These concepts are reflected in the repetition, regularity, spatial relationships, and systematic arrangement of motif elements. The results demonstrate that Batik Slobog Solo has substantial potential as a culturally grounded instructional resource that supports meaningful mathematics learning. This study contributes to ethnomathematics literature by expanding the scope of mathematical analysis on less-explored batik motifs and emphasizes the importance of integrating local cultural heritage into mathematics education to enhance conceptual understanding while promoting cultural preservation.